Utilizing Augmented Reality Technology to Increase Reading Interest in College Libraries - Pattiasina, Petrus Jacob (PT. Anagata Sembagi Education, 2025)
This study aims to describe the use of Augmented Reality (AR) technology to increase students' reading interest in university libraries. The method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation of students and librarians directly involved in the use of AR. The results show that the application of AR in catalogs and collection promotions can attract students' attention, increase motivation to visit the library, and foster interest in exploring reading collections. Students feel more motivated because the reading experience becomes interactive and enjoyable, while librarians consider AR effective as a medium for literacy promotion. Obstacles found include limitations in technological infrastructure, user devices, and the need for librarian training. Overall, the use of AR has been proven to make a positive contribution in connecting academic literacy with digital technology, making it relevant to support library transformation in the modern era.